Weathering phenomena, rock physical properties and long-term restoration intervention: a case study from the St. Johannis Chapel of Lütgenrode (Lower Saxony, Germany) - Siegesmund, Siegfried; Wiese, Frank; Klein, Calvin; Huster, Ulrich; Pötzl, Christopher (Environmental earth sciences, 2022)
"Small historical churches in rural villages are mainly functional buildings, lacking spectacular architectural or ornamental features. This is also true for the St. Johannis Chapel Lütgenrode near Göttingen (Lower Saxony, Germany), which dates back to the 13th century. The use of ca. 10 different natural building stones (Triassic sandstone and limestone, Holocene fresh water carbonate), scattered roof tiles and bricks result in a highly heterogeneous character of the chapel’s ascending walls. In addition, various repairs over the last centuries, using inadequate materials, amplified damages and produced critical stability problems, in particular at the southern wall. Here, the suitability of the dimensional stones are evaluated for construction and replacement purposes. A semi-quantitative distribution of lithotypes was performed, and weathering forms were mapped in detail. On-site analyses (micro-drilling resistance, the Schmidt hammer rebound test, capillary water absorption) provide data on the deterioration state of the main lithologies. The petrophysical data show that stratigraphically comparable building stones exhibit different technical characteristics and weathering behavior. All data serve to characterize the state of weathering and provide the data set to plan for future restoration work. The amount needed for restoration work has been estimated to be approximately 435,000–550,000 EUR. Because the local church authorities evaluate the significance of a church based on the frequency of its use, a secular use would be able to save the Lütgenrode chapel, but then the church political leaders would have to act quickly." (Abstract)